2003
DOI: 10.1074/jbc.m300633200
|View full text |Cite
|
Sign up to set email alerts
|

The CD8 T Cell Coreceptor Exhibits Disproportionate Biological Activity at Extremely Low Binding Affinities

Abstract: T lymphocytes recognize peptides presented in the context of major histocompatibility complex (MHC) molecules on the surface of antigen presenting cells. Recognition specificity is determined by the alphabeta T cell receptor (TCR). The T lymphocyte surface glycoproteins CD8 and CD4 enhance T cell antigen recognition by binding to MHC class I and class II molecules, respectively. Biophysical measurements have determined that equilibrium binding of the TCR with natural agonist peptide-MHC (pMHC) complexes occurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
10

Relationship

8
2

Authors

Journals

citations
Cited by 86 publications
(117 citation statements)
references
References 71 publications
5
112
0
Order By: Relevance
“…This result, in fact, has been observed in experiments by Sewell and coworkers (28), where a panel of MHC class I with mutated CD8 binding sites (11,28,29) was studied. They found that MHC mutants with a 10-fold weaker than WT affinity for CD8 were still able to activate T cells to the same extent (28). This result is consistent with our finding that the strength of CD8-MHC interactions that stabilize TCR-pMHC interactions contributes little to enhancing signaling.…”
Section: Discussionsupporting
confidence: 66%
“…This result, in fact, has been observed in experiments by Sewell and coworkers (28), where a panel of MHC class I with mutated CD8 binding sites (11,28,29) was studied. They found that MHC mutants with a 10-fold weaker than WT affinity for CD8 were still able to activate T cells to the same extent (28). This result is consistent with our finding that the strength of CD8-MHC interactions that stabilize TCR-pMHC interactions contributes little to enhancing signaling.…”
Section: Discussionsupporting
confidence: 66%
“…The above-proposed mechanism of CD8-TCR cooperation also explains how the weaker CD8-pMHC interaction compared with the TCR-pMHC one, has such a strong contribution in T-cell activation [49]. As suggested above, the pMHC complex formation with proximal CD8 and TCR is assumed to proceed at the rate determined by the CD8-pMHC association.…”
Section: Mechanism Of Pmhc Association With T-cellsmentioning
confidence: 80%
“…It seems extremely unlikely that the striking biophysical characteristics of the pMHCI/CD8 interaction have occurred by accident. Indeed, this conclusion is strengthened by the finding that the pMHCI/CD8 interaction is capable of exerting the vast majority of its biological function when weakened even further (21), which suggests that CD8 has specifically evolved to operate at very low solution affinities.…”
mentioning
confidence: 99%